A New Approach to the Classification of Voice Disorders - Nataraja NP; Jayaram M (Journal of All India Institute of Speech and Hearing, 1970)
Almost all branches of science are afflicted with a certain amount of ambiguity, inappropriateness and duplication in the use of terms for which Speech Pathology is not exception. In Speech Pathology, perhaps no other branch is afflicted more with this ambiguity in the usage of terms than the field of voice. Much of this semantic confusion in the field of voice is the heritage of pre-scientific ear when singers and singing teachers tried to describe what they felt when they sang and what they thought was actually happening (Broadnitz, 1959). Many of these terms that they coined are still in use and in doing so perhaps we are thinking in wrong  concepts.